Penerapan Sistem Manajemen Di Koprasi Konsumen Polres Jember Dalam Upaya Mensejahterakan Anggota - Indra Bayu Anggoro; Sayyid Perdana Putra; M. Mirza Hafif N.F (PT. Gudang Pustaka Cendekia, 2024)
Primkoppol, a cooperative designed to serve the needs of its police members, plays a crucial role in enhancing member welfare through various programs and services. This study aims to analyze the management system implemented by Primkoppol and how this system contributes to the improvement of its members' welfare. Employing a descriptive analytical approach, this research delves into the organizational structure, operational mechanisms, and strategies adopted by Primkoppol in executing its functions and objectives. Focusing on the evaluation of management practices, including resource management, profit allocation, and member development programs, this study seeks to identify the keys to success and the challenges faced by Primkoppol in its efforts to enhance member welfare. This analysis is supplemented with secondary data and direct survey results from members to capture their perceptions and experiences regarding the effectiveness of the services provided by Primkoppol. The findings indicate that Primkoppol has implemented various positive initiatives oriented towards improving member welfare, including innovations in financial services, enhancement of product and service quality, and member capacity development through education and training. However, there is also room for improvement, especially in terms of enhancing management transparency, operational efficiency, and adaptation to digital technology. This study concludes that to continue improving its members' welfare, Primkoppol needs to further optimize an adaptive and responsive management system to environmental changes and member needs. Recommendations include improvements in two-way communication between management and members, integration of information technology, and strengthening of institutional capacity.